السوق السياسية في العراق بعد عام 2003 : دراسة في النشأة والديناميكيات - Saleem, Dr. Zmkan Ali (Journal of Legal and Political Studies, 2025)
Since the regime change in 2003, the political landscape in Iraq has been shaped by entrenched patterns of transactional politics and politically motivated violence. Political elites, regardless of their ideologies or ethnic and sectarian affiliations, have routinely exchanged political loyalty for material gains, while various factions and figures have resorted to coercion and violence as strategic tools for negotiating, consolidating, or maintaining power. These dynamics have contributed to undermining state legitimacy, depleting public resources, and weakening formal institutions. This raises a crucial question: how can the continued use of money and violence—the two main instruments of political power—be systematically understood within the broader context of post-2003 Iraq, particularly in relation to their impact on political stability and institutional development? Based on the Political Marketplace Framework, this study investigates the origins, evolution, and dynamics of bargaining and violence in three strategic Iraqi governorates—Nineveh, Basra, and Diyala—between 2003 and 2020. The temporal focus and subnational case studies help to deepen the analysis and highlight the importance of local political arenas in shaping the broader political market in Iraq. The findings indicate that political power at the local level is maintained through a combination of coercive power and bargaining. Moreover, alliances among elites often transcend sectarian and ethnic lines, challenging prevailing narratives about identity-based politics in post-2003 Iraq. The prioritization of patronage and the buying of loyalties over the delivery of public services has led to governance deficits and chronic instability. Keywords: Political Marketplace, Iraq, Dynamics
Keywords: Keywords Political Marketplace; Iraq; Dynamics